Melatonin modulates hypoxia-induced changes of rat brain excitability - Maresova, Dana; Riljak, Vladimir; Mares, Jan (General physiology and biophysics, 2010)
The aim of our study was to test the hypothesis, if melatonin pre-treatment (in dose of 100 mg/kg) can influence the changes of brain function after short-term hypoxia exposition (simulated altitude 9000 m) in young immature rats. Experiments were performed on freely moving 12-, 25- and 35-day-old male Wistar rats. One hour prior to hypoxia exposition, animals were pre-treated with melatonin and 24 hours after hypoxia cortical afterdischarges (ADs) were elicited by repeated stimulation of the right sensorimotor cortex. The duration of evoked ADs and shape of evoked graphoelements was monitored. Short-term exposure to hypoxic conditions resulted in significantly shorter ADs duration in 12-day-old rats after stimulations (except the 2nd one stimulation) compared to control group. Administration of melatonin prolonged the duration of ADs after all stimulations except the 1st one. Analysis of the duration ADs revealed no significant changes, either after the exposition to hypobaric hypoxia or after melatonin administration in 25- and 35-day-old animals. Effects and mechanisms of melatonin action on the brain seizure susceptibility and the possible beneficial role of that treatment in hypoxic brain damage are discussed.
Keywords: elektrokardiografie; Rats; akční potenciály; Action Potentials; Hypoxia, Brain; mozková hypoxie; Rats, Wistar; mužské pohlaví; mozek; krysa rodu Rattus; Brain; Electrocardiography; Nerve Net; zvířata; Melatonin; nervová síť; melatonin; potkani Wistar; Male; Animals